Trace ppb-level NH3 sensor based on single petal-like Ce-doped SnO2. (April 2023) - Yuan, Yuting; Zhan, Guanghui; Peng, Weizhong; Huang, Chao; Chen, Hande; Lin, Shiwei
Abstract: Gas sensors have been broadly researched for room temperature (RT) and real-time applications. However, it has been discovered that humidity affects the sensing and the sensor's lifespan at RT. Thus, we must develop new sensing materials with high sensitivity and stability at RT. During this research, the Ce–SnO2 gas sensor was produced by the one-pot hydrothermal method. As fully confirmed by scanning electron microscopy, transmission electron microscopy, and X-ray photoelectron spectrometry, Ce doping changes the morphology of the original SnO2 nanoarray and generated large oxygen vacancies. The sensor of Ce–SnO2 -5(Ce wt% = 5 wt%) has a higher sensing performance for NH3 at RT and high humidity (ΔR/R0 = 33.62% at 30 ppb, 4.4 s/12.8s), and the limit of detection (LOD) reaches 780 ppt, which exceeds most of the recently reported similar metal oxides. Besides, the sensor also has an apparent anti-interference ability to some reduced gases and has better stability and repeatability. The sensing process improvement is explained as follows: the oxygen vacancy, large specific surface area, and redox cycling of Ce ions between the two valence states increase surface activity and charge transfer efficiency. Graphical abstract: Image 1 Highlights: The sensor's sensitivity has been enhanced by the combined effect of Ce doping and oxygen vacancy modulation. Experimental analyses show that Ce doping and higher oxygen vacancy concentrations enhance the adsorption capacity of SnO2 for NH3 . Prepared sensors could trace ppb-level NH3 and are theoretically detectable at a minimum concentration of 780 ppt NH3 .